2008
DOI: 10.1007/s11547-008-0245-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of breast Magnetic Resonance Imaging (MRI) in patients with unilateral nipple discharge: preliminary study

Abstract: Breast MRI can be considered a valuable examination in the diagnosis of suspected ductal disease and an alternative to galactography when the latter cannot be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…16 Its routine use in patients with a breast lesion is nonetheless limited by its relatively low specificity of 72% (95% confidence interval, 67%-77%). 17 The role of magnetic resonance imaging in patients with nipple discharge has been extensively validated, [18][19][20][21] suggesting that it may detect or exclude the presence of carcinoma with a high degree of certainty. Magnetic resonance imaging may be considered when all other available strategies are inconclusive.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…16 Its routine use in patients with a breast lesion is nonetheless limited by its relatively low specificity of 72% (95% confidence interval, 67%-77%). 17 The role of magnetic resonance imaging in patients with nipple discharge has been extensively validated, [18][19][20][21] suggesting that it may detect or exclude the presence of carcinoma with a high degree of certainty. Magnetic resonance imaging may be considered when all other available strategies are inconclusive.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Although not a routine practice in the United Kingdom; a number of techniques have been used to determine the cause of nipple discharge, beyond the triple assessment. Nipple discharge cytology has a low sensitivity for the detection of breast cancer (19) and is unlikely to alter the management of patients with nipple discharge (20) . Hadfield's procedure and microdochectomy are the most common techniques for the surgical treatment of patients with nipple discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The most common sonographic features are duct dilatation, particularly in cases associated with solid internal echoes and duct wall thickening in generally central and/or subareolar areas (Ballesio et al, 2008). Berg & Gilbreath (2000) reported that US identified 45 of 48 (94%) invasive tumor foci and 7 of 16 (44%) foci of DCIS while only 9 of 64 (14%) malignant foci were detected by US.…”
Section: Ultrasonography (Us)mentioning
confidence: 99%
“…In addition to the patient's clinical history and cytological evaluation of the ND, performing a US-guided FNA is fundamental for differentiating between malignant and benign lesions (Ballesio et al, 2008citing Sardanelli et al, 1997.…”
Section: Ultrasonography (Us)mentioning
confidence: 99%
See 1 more Smart Citation